Pengaruh Social Media Marketing Dan Brand Image Terhadap Minat Beli Produk Mari Oppa (Studi Kasus Pada Followers Akun Instagram @Marioppa.Id) - Rahmadhani, Sahrul Fizky; Siregar, Salim (Peneliti.net, 2024)
This research aims to analyze the influence of social media marketing and brand image on purchase intention Mari Oppa products using quantitative methods and descriptive verification analysis. Sampling used a non-probability sampling method with purposive sampling, which resulted in a total sample of 391 respondents. The analysis technique used is multiple linear regression analysis and hypothesis testing using the t test and f test using SPSS 25 tools. The research results show that there is a partial and simultaneous influence between social media marketing and brand image on purchase intention.